KREATIVITAS GURU DALAM MENINGKATKAN KOMPETENSI PROFESIONAL (STUDI KASUS Di MI MA’ARIF PATALAN): (Studi Kasus di Mi Maarif Patalan) - Daluti Delimanugari; Galuh Sandra Pangesti; Umi Musaropah; Mustolikh Khabibul Umam (PrimEarly : Jurnal Kajian Pendidikan Dasar dan Anak Usia Dini, 2022)
This study discusses the Description of Class Teacher Professional Competence at Mi Ma'arif Patalan and his Creativity in Improving the Professional Competence of the Class Teacher. This research is a field work (field work research) with a qualitative approach. Data collection in this study uses observation, documentation, and interviews. Analysis of the data used in this study through data reduction, data display, and verification. Test the validity of the data in this study using triangulation. The results of this study indicate that in general, the professional competence of teachers at MI Ma'arif Patalan which was sampled as many as six teachers by this writer is good enough, but needs to be improved again especially in developing professionalism in a sustainable manner by taking reflective action. Most of the class teachers at MI Ma'arif Patalan have achieved professional competence. That is because teachers creatively seek to improve their professional competence in the following ways: (1) utilize information and communication technology, (2) use reward and punishment learning methods, (3) develop themselves by attending educational seminars and discussions between the teacher, (4) is creative in making learning media, and (5) uses the natural environment as a source of learning.